An Analysis Of Flow Capacity Variation and Distance Between Louvered Strip Constant Angle 25o Of Heat Transfer and Pressure Decrease On The Heat Exchanger - Ishak Usman; Kifli Umar; Sandi Rais; Rian A. Rahman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to determine the effect of variations in flow rate and the louvered strip inclination angle on heat transfer in a double-pipe heat exchanger and the impact of variations in flow rate and inclination angle of the louvered strip on the inner tube pressure drop in a double-pipe heat exchanger. Three pieces of louvered strips at 50 mm, 70 mm, 90 mm are inserted into the inner tube of the heat exchanger with a constant tilt angle of 25°. Cold and hot water are used at a constant value where the cold-water flow rate is 600 liters/hour and V = 900 liters/hour, while the hot water flow rate is 1200 liters/hour. The inlet and outlet temperatures of both hot and cold water are measured, and the heat transfer characteristics of the heat exchanger are calculated as a result of the pressure drop that occurs in the inner tube due to the difference in height on the U-tube manometer used.